Inoculation With Growth-Promoting Bacteria Azospirillum brasilense and Its Effects on Productivity and Nutritional Accumulation of Wheat Cultivars - Boleta, Eduardo Henrique Marcandalli; Shintate Galindo, Fernando; Jalal, Arshad; Santini, José Mateus Kondo; Rodrigues, William Lima; Lima, Bruno Horschut de; Arf, Orivaldo; Silva, Marcelo Rinaldi da; Buzetti, Salatiér; Teixeira Filho, Marcelo Carvalho Minhoto (Frontiers in Sustainable Food Systems, 2020)
The agricultural practices that allow productive increase in a sustainable manner is becoming increasingly necessary to feed an ever-growing global population. The inoculation with A. brasilense has the potential to reduce the use of synthetic mineral fertilizers with efficient capacity to promote plant growth and increase nutrition. Therefore, this research was developed to investigate the potential use of Azospirillum brasilense to increase the accumulation of macro and micronutrients, and its influence on grain yield in two wheat cultivars (CD1104 and CD150), under irrigated conditions in the Brazilian Cerrado. The study was carried out in a Rhodic Hapludox under no-till system. The experiment was designed in a randomized blocks with six replications, arranged in a 2 x 2 factorial scheme: 2 cultivars (CD150 and CD1104), 2 levels of inoculation (control and with A. brasilense). The inoculation with A. brasilense provided greater accumulation of micronutrients, such as B, Cu, Fe and Mn by 33.6%, 14.4%, 26.9% and 14.8% respectively in the shoot of wheat. The cultivar CD150 has greater efficiency to accumulat N (+35.5 kg N ha -1) as compared to cultivar CD1104. Interactions between inoculation and cultivars resulted in greater accumulation of S and K in shoot of wheat cultivar CD150, as well greater accumulation of Cu in CD1104. Inoculation or cultivars did not statistically influence wheat grain yield. However, the CD1104 genotype inoculated with A. brasilense resulted in +7.1 bags (60 kg) ha-1 in relation to control. Inoculation can contribute more sustainably to wheat nutrition.